Prevalence of CA 27.29 in primary breast cancer patients before the start of systemic treatment - Rack, Brigitte K.; Schindlbeck, Christian; Jückstock, Julia; Genss, Eva-Maria; Hepp, Philip; Lorenz, Ralf; Tesch, Hans; Schneeweiss, Andreas; Beckmann, Matthias W.; Lichtenegger, Werner; Sommer, Harald; Friese, Klaus; et al. (Anticancer research, 2010)
Background: Several trials show that tumor markers at primary diagnosis of cancer have prognostic relevance and can predict dissemination of the disease. While MUC-1 markers are frequently used to monitor treatment efficacy in metastatic breast cancer, their role at primary diagnosis or during follow-up remains unclear. This translational research project within the SUCCESS trial evaluates the role of the tumor marker CA 27.29 before and after adjuvant chemotherapy, as well as after two and then five years in patients with early breast cancer. Patients and Methods: The SUCCESS trial compared FEC (500/100/500)-docetaxel (100) vs. FEC (500/100/500)-docetaxel/gemcitabine (75/2000) and two vs. five years of zoledronate treatment in node-positive and high-risk node-negative patients with primary breast cancer. CA 27.29 was measured before chemotherapy in 2669 patients with the reagent ST AIA-PACK CA 27.29 for AIA-600II-Analyzer (Tosoh Bioscience, Belgium). Results of CA 27.29 above 31 U/ml were regarded as positive. Results: 7.6% of patients had elevated marker levels after the completion of primary surgical treatment but before initiation of chemotherapy (n=202, mean 19, range 3-410 U/ml). No correlation between nodal status (p=0.55), grading (p=0.85), hormonal status (p=0.21), HER2/neu status on the primary tumor (p=0.58) and CA 27.29 was shown. However, larger tumor size (p=0.02), lobular histology (p<0.0001), older age (p<0.001) and postmenopausal hormone status before the start of treatment (p=0.006) were significantly associated with higher CA 27.29 levels. Conclusion: These data indicate a close relationship between CA 27.29 and tumor mass persisting even several weeks after surgery, but also identify potential confounding factors that should be considered in interpreting tumor marker results. Further follow-up of the SUCCESS trial will clarify whether CA 27.29 measured after surgery but before the start of systemic treatment is prognostically relevant and whether it is a useful marker for treatment monitoring in the adjuvant setting.
Gesehen am 09.05.2023